Function and Characterization of an Alanine Dehydrogenase Homolog From Nocardia seriolae - Chen, Guoquan; Tan, Ziyang; Liu, Yansheng; Weng, Tingting; Xia, Liqun; Lu, Yishan (Frontiers in Veterinary Science, 2022)
Fish nocardiosis is a chronic, systemic, granulomatous disease in aquaculture. Nocardia seriolae has been reported to be one of the main pathogenic bacteria of fish nocardiosis. There are few studies on the associated virulence factors and pathogenesis of N. seriolae. Alanine dehydrogenase (ALD), which may be a secreted protein, was discovered by analysis of bioinformatics methods throughout the whole genomic sequence of N. seriolae. Nevertheless, the roles of the ALD and its homologs in pathogenesis of N. seriolae are not demonstrated. In this study, the function of N.Seriolae ALD (NsALD) was preliminarily investigated by gene cloning, host cell subcellular localization, secreted protein identification and cell apoptosis detection. Extracellular products identification of N. seriolae via Mass spectrometry (MS) analysis revealed that NsALD was a secreted protein. In addition, subcellular localization of NsALD-GFP recombinant protein in fathead minnow (FHM) cells showed that the strong green fluorescence co-localized with mitochondria. Moreover, apoptosis assays demonstrated that the overexpression of NsALD induces apoptosis in FHM cells. This study may lay the foundation for further exploration on the function of NsALD and facilitate the further understanding of the pathogenic mechanism and the associated virulence factors of N. seriolae.